Management of Drip Irrigation and Fertilizer Injection on Potato Crop in Semi-Arid Climate - Ashraf Yaqoub Sweidan; Nourdin Salem Blaq; Nesrin Elmabrouk Gremida (African Journal of Advanced Pure and Applied Sciences, 2023)
This study was carried out to investigate the effect of water regime under a drip irrigation system on growth, tuber quality, leaf total chlorophyll, free proline and mineral composition, and water relations of potato crops during 2021-2022 growing season of the potato crop. The texture of the experimental site was sandy. Imported potato tuber seeds (Solanum tuberosum, L.) of Diamond cultivar were used in the present study. Planting was done in October 2021, in wet soil. The potato tuber seeds were planted at 0.22 m apart, in rows of 0.80 m width and 40.0 m length. Irrigation water was applied throughout a drip irrigation network using drippers of 3.0 L/hr capacity. The irrigation water was applied at six frequencies: 50, 75, 100, and 125% of reference evapotranspiration. The results revealed that foliage characteristics (i.e., plant height, shoot fresh weight, shoot dry weight, shoot dry matter and shoot water content) were significantly affected by the irrigation regime, in which increasing the amount of Irrigation water increased the vegetative growth. The data also, clearly indicated that increasing irrigation significantly increased leaf characteristics (total chlorophyll, leaf water contents i.e., free water content (FWC), bound water content (BWC), total water content (TWC), and relative water content (RWC)). Leaf proline content substantially increased with increasing water stress (decreasing the amount of irrigation water). Increasing the amount of irrigation water resulted in increasing the leaf nutrient content. Irrigation at 100% of ET0 resulted in improving the potato tuber’s physical and chemical characteristics. The maximum tubers yield was attained at 100% of ET0 treatment (32.36 tons/ha.). In addition, the maximum water use efficiency was attained at the same level of irrigation water (17.249 kg tubers/ m3 of applied water). The most soil moisture was extracted from the top 40 cm soil layer. The moisture extraction was increased significantly with increasing the amount of irrigation water. The optimum soil moisture tension for potato crops was between 0.25 and 0.35 bar. The most important outcomes from the present study are clarifying the important role of irrigation regime with drip irrigation system in improving potato growth and tuber yield. Also, good distribution of moisture overall the root zone depth, can enhance the plant growth and yield of potato crops. The present study recommends 90% of ET0 (1238.3 m3 of applied water/fed) to achieve the highest potato yield and tuber quality under the same present conditions.